2018
DOI: 10.14744/scie.2018.66375
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii, Rubella and Cytomegalovirus Among Pregnant Refugees and Turkish Women: A Retrospective Comparative Study

Abstract: Objective:To evaluate the prevalence of Toxoplasma gondii, rubella, and cytomegalovirus (CMV) among pregnant Turkish women as well as Syrian refugees in Istanbul. Methods:Among pregnant women who were admitted to the Esenler , antibodies against T. gondii, rubella, and CMV were measured using the micro-ELISA method. The test results were evaluated retrospectively. Results:Out of a total of 1066 pregnant women screened in the present study, 963 (90.3%) were Turkish, and 103 (9.7%) were Syrian refugees. IgM posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…[30] When the studies on rubella virus seroprevalence in pregnant women in Turkey were evaluated, the lowest rubella IgG positivity with a rate of 86.6% was in Van and the highest seropositivity with a rate of 97.5% was in Isparta (Table 1). [14,17,20,22,23,28,[31][32][33][34][35][36] In this study, rubella IgG seropositivity rate which is 91.7% was a little lower than that of regional data, however, it is consistent with overall data in our country. Our results reveal that there is a rubella virus-responsive pregnant with a rate of 8%.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[30] When the studies on rubella virus seroprevalence in pregnant women in Turkey were evaluated, the lowest rubella IgG positivity with a rate of 86.6% was in Van and the highest seropositivity with a rate of 97.5% was in Isparta (Table 1). [14,17,20,22,23,28,[31][32][33][34][35][36] In this study, rubella IgG seropositivity rate which is 91.7% was a little lower than that of regional data, however, it is consistent with overall data in our country. Our results reveal that there is a rubella virus-responsive pregnant with a rate of 8%.…”
Section: Discussionsupporting
confidence: 83%
“…[37] In studies on CMV IgG seropositivity rates in pregnant women in Turkey, the rate was generally more than 90% (Table 1). [14,[20][21]23,28,[32][33][34][35][38][39][40] In this study, while CMV IgG seropositivity was 99.3%, IgM seropositivity was 14.7%. These results reveal that most of the women of childbearing age face CMV before pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…These lower results may be attributed to the life style of Eritrean women, like consumption of properly heated and cooked food, and less contact with domestic animals. We found the prevalence of TORCH IgG to be much lower compared to the results of studies that were conducted in Saudi Arabia, India and Turkey [3][4][5][6]11,12 .…”
Section: Discussioncontrasting
confidence: 68%
“…In our study, we determined the anti-Toxoplasma IgG and anti-Toxoplasma IgM seropositivities in pregnant women as 36.3% and 1.0%, respectively. According to different studies conducted in Turkey, anti-toxoplasma IgG positivity was found between 30.1% and 69.5% (6,(7)(8)(9). The overall rate of seropositivity for T. gondii antibodies has been reported to reach as high as 85% In Turkey (11).…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of seropositivity for T. gondii antibodies has been reported to reach as high as 85% In Turkey (11). In recent research in Istanbul, toxoplasma seropositivity was detected between 31% and 26.3% in pregnant women (7,9). Toxoplasmosis prevalence varies in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%